Preliminary study on coconut oil extraction at ambient conditions - Pui Yun Kiong (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
The objectives of this project were to determine the effect of the temperature in each of the extraction method, to study the effectiveness of subcritical solvent extraction in comparison with supercritical solvent extraction in the previous studies and also to analyse the composition and thermal characteristic of product. . Overall extraction and separation were constant at 120 minutes. The product was investigated through the Fourier Transform Infra-red Spectroscopy (FTIR), and Differential Scanning Calorimetry (DSC). From the result, the yield of water bath extraction was less than simple distillation. . Coconut oilwas showed the melting range which was comparable to DSC at scanning rate of 2 K/min.In conclusion, water bath extraction was able to extract more yields from coconut oil compared to simple distillation in same temperature and pressure. The advance extraction method which is supercritical solvent extraction is more advantageous in purification of octanol.